A Case of Oculomotor Nerve Paralysis Caused by Cavernous Sinus Metastasis of Tonsil Cancer - Younghac Kim; Man Ki Chung; Sang Duk Hong (Journal of Rhinology, 2022)
Oropharyngeal squamous cell carcinoma (OSCC) with metastasis to the cavernous sinus (CS) is uncommon, and only a few cases have been described in the literature. The highest age-adjusted incidence rate for OSCC including the tonsil in males occurs in South Asians, and more cases should be reported to establish earlier identification and treatment. We report a case of OSCC in a 59-year-old male who underwent prompt endoscopic biopsy and early palliative radiation therapy to allow complete recovery of cranial nerve palsies to improve his quality of life, despite having a poor prognosis. Furthermore, this report emphasizes his dramatic resolution of symptoms after radiation therapy, highlighting the importance of rapid recognition and proper management.